Assistance and Empowerment of MSES: Aoplication of Flower Preservation Methods and Simple Accounting to Increase the Income of the Retirement Age Community in Sukapada Village, Cibeunying Kidul District, Bandung City - Gatot Santoso; Magnaz Lestira Oktaroza (Universitas Islam Bandung, 2023)
Assistance and empowerment are carried out for Small and Medium Enterprises (MSMEs –Retirement Age) actors with preserved flower products and the application of SimpleAccounting in the Sukapada sub-district, Cibeunying Kidul District, Bandung City. Based onthe results of the PKM Team's survey, information was obtained that Sukapada Village,Cibeunying Kidul District, is the northernmost village in Cibeunying Kidul District, most ofthe residents are retirees from various jobs who gather together daily to carry out worship andsports activities. Furthermore, information was obtained that in the Sukapada Village therewere several groups of residents who were flower craftsmen trying to develop decorativeflower crafts. The constraints currently faced by flower makers in the Sukapada sub-district arefast wilting flowers, non-uniform flower diameters and blooming rates. Based on the conditionsmentioned above, the PKM Team intends to help improve the quality of these ornamentalflowers to become ornamental flowers that last for more than 1 year so that they have highselling power by implementing a preservation process. Assistance and empowerment is carriedout through training on flower preservation, training on making simple bookkeeping, trainingon website management for online shopping, and product registration in the form of preservedflowers in several market places. Through the training conducted, business people have beenable to produce quality preserved flowers and calculate the cost of the product and the sellingprice of the preserved flowers. In addition, they are also able to always maintain the websiteand market place they already have so that they can be used all the time to increase profitablesales volume and increase the income of these business people.